Clinicopathologic Findings of Spontaneous Leukemia in 9 Pet African Hedgehogs (Atelerix Albiventris) - Koizumi, Iori; Hernandez-Muguiro, Daniela; Chu, Shelley Ann Ash; Stokol, Tracy; Asakawa, Midori Goto (Frontiers in Veterinary Science, 2020)
Previous reports of leukemia in hedgehogs are limited. We describe clinicopathologic features of leukemia in 9 hedgehogs, including eosinophilic leukemia (n=3) and acute leukemia/leukemic phase of lymphoma (n=6). All 3 hedgehogs with eosinophilic leukemia were older than 2 years of age; in contrast, 4 of 6 cases of acute leukemia/lymphoma were less than 2 years old. Hedgehogs presented for non-specific clinical signs of anorexia and lethargy. On hematologic testing, hedgehogs with eosinophilic leukemia had a marked leukocytosis, consisting mostly of eosinophilic precursors with fewer mature eosinophils, whereas there were 43-97% immature cells (blasts) in the blood of hedgehogs with acute leukemia/lymphoma. Anemia (n=6) and/or thrombocytopenia (n=6) were concurrent findings. Increased liver enzyme activities (alanine aminotransferase, alkaline phosphatase) and hypoalbuminemia were the common findings on biochemical panels. All cases of eosinophilic leukemia and 4 cases of acute leukemia/lymphoma died shortly after diagnosis (median 7 days, range 0-41 days), whereas 2 cases of acute leukemia/lymphoma lived for 94 or 101 days. Postmortem examination in 5 cases (1 eosinophilic leukemia, 4 acute leukemia/lymphoma) showed bone marrow infiltrates, confirming eosinophilic leukemia and acute leukemia in 1 and 3 cases, and bone marrow necrosis in 1 animal with acute leukemia/lymphoma. Immunohistochemical staining of bone marrow sections confirmed a T-cell acute leukemia in 1 case. Several hedgehogs had concurrent carcinomas. Hedgehogs suffer from eosinophilic leukemia and acute leukemia/lymphoma. However, classification of acute leukemia by lineage was not possible due to lack of hedgehog cross-reactive or species-specific reagents.